If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying t + 36 = 13 Reorder the terms: 36 + t = 13 Solving 36 + t = 13 Solving for variable 't'. Move all terms containing t to the left, all other terms to the right. Add '-36' to each side of the equation. 36 + -36 + t = 13 + -36 Combine like terms: 36 + -36 = 0 0 + t = 13 + -36 t = 13 + -36 Combine like terms: 13 + -36 = -23 t = -23 Simplifying t = -23
| Q=p^2+3T | | -x+4=-24 | | -4x(6x-6)+3x= | | -4y+4=-8y-28 | | 2x+13c+x-5c=90 | | r^2+5r-104=0 | | 5y+30=5x | | 3x^3-19x^2+33x-9=0 | | m+1=4 | | -6y+4+11y=-6 | | 5y+30=5y | | 2x+13cx-5c=90 | | y-4=-2(x-2) | | y-2=-2(x-4) | | s^2+2s-24=0 | | 4x^2-3-11=0 | | 5(y-2)-7y= | | y-3=1(x-4) | | 8x+4+4x+7=11x+3 | | y-3=1(x-3) | | 2r^2+2r-14=0 | | 2(3x-4)-3(x+1)=4 | | x*073=1.752 | | y-4=1(x-3) | | -r=110 | | y-8=2(x-3) | | y-3=2(x-9) | | -(z+1)+2(2-2)= | | 8+z=-8 | | X+40=20 | | 37=5m-3m | | 3+x=-11 |